Pengaruh Manajemen Inventory terhadap Ketersediaan Produk Kosmetik di Gudang PT Radysa Dharma Abadi - Aprialdo Abdinata Sitanggang; Cyntia Paramita; Dian Sepbila; Noel T.P Hutahaean; Artha Putri Br. Karo (Jurnal Riset Manajemen dan Akuntansi, 2026)
Inventory management is a crucial factor in ensuring optimal product availability in distribution warehouses, particularly in the cosmetics industry, which is characterized by fluctuating demand and a limited shelf life. This study aims to analyze the influence of inventory management on the availability of cosmetic products at PT Radysa Dharma Abadi using a qualitative approach. Data were collected through in-depth interviews and direct observation with warehouse managers and operational staff. The research results show that the implementation of the FIFO (First-In, First-Out) method is effective in reducing the risk of product expiration. However, there are inconsistencies between physical stock and system data due to sub-optimal control and human error. Near-expired products and product returns pose challenges that require strategies such as returning products to suppliers and sales promotions for older stock. Barcode technology helps accelerate real-time stock data updates, but rigorous training and strict supervision are needed to enhance the accuracy of record-keeping and inventory control. The integration of technology, sound procedures, and skilled human resources (HR) are key to successful inventory management. Recommendations include improving the stock monitoring system, developing HR competence, managing near-expired products, and enhancing coordination with suppliers and logistics/expedition services to maintain efficient distribution and ensure products arrive in prime condition. This research contributes to the development of inventory management systems in the cosmetics industry to improve customer satisfaction and corporate competitiveness.